2017
DOI: 10.1016/j.rmcr.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A case report of EGFR mutant lung adenocarcinoma that acquired resistance to EGFR -tyrosine kinase inhibitors with T790M mutation and epithelial-to-mesenchymal transition

Abstract: Although a secondary mutation and the epithelial-to-mesenchymal transition (EMT) are encountered very often in patients received the EGFR-TKI targeted treatment. The entire detrimental morphological change of the cancer entity was rare reported. Herein we report a case that acquired resistance to EGFR-TKI with T790M mutation and complete EMT morphological change of the tumor tissue. The primary lung tumor from a 52-year-old woman was diagnosed with moderate differentiated adenocarcinoma, with intensively posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Only few clinical reports evaluated EMT in patients with tumors harboring activating EGFR mutations. Those observations associated mesenchymal features with EGFR-TKI resistance [Miyoshi et al, 2015;N. Zhang et al, 2017;Poh et al, 2018].…”
Section: Egfr-tki Resistancementioning
confidence: 87%
“…Only few clinical reports evaluated EMT in patients with tumors harboring activating EGFR mutations. Those observations associated mesenchymal features with EGFR-TKI resistance [Miyoshi et al, 2015;N. Zhang et al, 2017;Poh et al, 2018].…”
Section: Egfr-tki Resistancementioning
confidence: 87%
“…This demonstrates a major pitfall of utilizing single targeted therapies in the clinic; the mechanism of drug resistance has a secondary effect of increasing the metastatic potential of the tumor. EMT has also been identified as a mechanism of drug resistance in EGFR T790M-driven cancers (28,29,55), suggesting that this may be a common phenomenon among RTK gatekeeper mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The gatekeeper mutants of EGFR, PDGFR, c-ABL, and Src were shown to have activated kinase activity and an increased rate of cellular transformation (16). In addition, the EGFR T790M gatekeeper mutation has been shown to promote EMT (28)(29)(30). Previous studies in our lab have kinetically characterized V561M FGFR1 and demonstrated an increase in the k cat of V561M FGFR1 relative to wild type (WT).…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, analysis of a primary tumor sample from a patient with EGFR-TKI-resistant lung ADC showed a complete EMT phenotype with the T790M mutation. 132 The role of IGF1R signaling in the development of EGFR-TKI resistance is well known 133 ; thus, Li et al further explored the mechanism of IGF1R signalling-mediated EGFR-TKI resistance in lung cancer. It was revealed that IGF1R/Akt/Erk/NF-κB signaling is activated during EMT-mediated EGFR-TKI resistance in EGFR-mutated NSCLC.…”
Section: Pik3ca Mutationmentioning
confidence: 99%
“…These results strongly support that EMT phenotype plays an important role in sensitivity and resistance of EGFR‐TKIs in lung cancer. Furthermore, analysis of a primary tumor sample from a patient with EGFR‐TKI‐resistant lung ADC showed a complete EMT phenotype with the T790M mutation 132 . The role of IGF1R signaling in the development of EGFR‐TKI resistance is well known 133 ; thus, Li et al further explored the mechanism of IGF1R signalling‐mediated EGFR‐TKI resistance in lung cancer.…”
Section: Other Mechanisms Responsible For Resistance To Egfr‐tkis In mentioning
confidence: 99%